2022
DOI: 10.1016/j.amsu.2021.103092
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-221 and tamoxifen resistance in luminal-subtype breast cancer patients: A case-control study

Abstract: Background Around 70% of breast cancers (BCs) are estrogen receptor-α (ERα)-positive. Adjuvant endocrine therapy is used to reduce estrogen levels and inhibit signal transduction through the ER. The anti-estrogen drugs that are most commonly used in endocrine therapy belong to the selective ER modulator (SERM) class and include tamoxifen. Although it has been used for three decades in cases of early-stage and ERα-positive BC, resistance to tamoxifen is a common problem. microRNAs (miRNAs) have a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…In particular, recent studies report that miRNAs contributed to the progression of breast cancer after tamoxifen treatment. The mechanisms include the activation of estrogen receptor alpha (ERα), progression of the cell cycle, regulation of apoptosis, and controlling epithelial-to-mesenchymal transition [68][69][70][71]. For these reasons, studies of differentially expressed miRNAs (DEMs) are similar to the research of differentially expressed genes (DEGs) to improve the susceptibility of tamoxifen against breast cancer and provide novel insights for clinical doctors.…”
Section: Ivyspringmentioning
confidence: 99%
“…In particular, recent studies report that miRNAs contributed to the progression of breast cancer after tamoxifen treatment. The mechanisms include the activation of estrogen receptor alpha (ERα), progression of the cell cycle, regulation of apoptosis, and controlling epithelial-to-mesenchymal transition [68][69][70][71]. For these reasons, studies of differentially expressed miRNAs (DEMs) are similar to the research of differentially expressed genes (DEGs) to improve the susceptibility of tamoxifen against breast cancer and provide novel insights for clinical doctors.…”
Section: Ivyspringmentioning
confidence: 99%
“…Distinguished studies also showed us that numerous studies of non-coding RNA especially miRNA play important roles in ET resistance, such as miRNA such as miRNA-1972, miRNA-375 and miRNA-221. 52,88 However there are still no clear depiction of p53 roles in ET resistance caused by miRNA involvement. It is due to the complexity of the network of both parties, in which miRNA could regulate p53 level and function and vice versa mutated p53 could regulate the miRNA expression and modulate miRNA biology activities due to its gain-of-function properties.…”
Section: Estrogen and Estrogen Receptormentioning
confidence: 99%
“…Distinguished studies also showed us that numerous studies of non-coding RNA especially miRNA play important roles in ET resistance, such as miRNA such as miRNA-1972, miRNA-375 and miRNA-221. 52 , 88 …”
Section: P53 Roles In Tumor Microenvironment In Et Resistant Bc and N...mentioning
confidence: 99%
“…miR-221 can be considered a potential biomarker of tamoxifen resistance. It was shown in a case-control study that serum miR-221 expression level is higher in tamoxifen-resistance luminal-subtype breast cancer patients with local recurrence and metastasis than in patients without progression [ 191 ]. Additionally, the inhibition of miR-221 and miR-222 restored the sensitivity of tamoxifen-resistant breast cancer cell line (MCF-7 TamR) cells to tamoxifen [ 192 ].…”
Section: Clinical Significance—diagnosis and Therapymentioning
confidence: 99%